When can culturally diverse teams be more creative? The role of leaders' benevolent paternalism - Lu, Lin (2019)
The current research examines the conditions under which cross‐cultural teams can realize their creative potential—a consequence of their cultural diversity. We propose that in more culturally diverse teams, team members are less open when communicating with each other, which impairs the team's ability to elaborate on the information contributed by different members, ultimately limiting team creativity. We further theorize that leaders' benevolent paternalism, a leadership style that is particularly prevalent in East Asian contexts, can reduce the negative consequence of intercultural diversity on intercultural communication openness. Based on multi-wave, multi-source data from 48 culturally diverse teams in China, we found that perceived intercultural diversity is negatively related to intercultural communication openness, which, in turn, is positively related to information elaboration, and ultimately, team creativity. Leader benevolent paternalism attenuates the negative relationship between intercultural diversity and intercultural communication openness. These findings enrich the literature on intercultural diversity by calling attention to communication‐related obstacles.